Sentosa Bank Customer Encrypted Data Information System Using Micro SD - Nurcahya, Saputra Dwi; Purwanti, Purwanti; Nazelliana, Dian (Journal of Information System, Informatics and Computing, 2022)
Bank is one of the important companies both domestically and abroad. With a focus on savings and loans for financial or financial problems, Banking is able to assist the government in securing public money and assisting the community also in terms of borrowing money for business capital or other purposes. Large amounts of money storage make Banking one of the companies that are continuously monitored by parties who do not responsible, whether thieves, robbers, hackers, crackers, carding, or other malicious plans whose purpose is to take funds or use customer money stored for their personal needs. One of the crimes currently rife in banking cases is breaking into customer accounts and stealing money at ATMs by knowing the customer's account number and ATM PIN. Therefore, our group creates a security system to maintain the security of customer data, both in terms of authentication, access rights, integrity and other security factors. One way to secure customer accounts, especially Bank Sentosa customers, is to create a customer data encryption system and application login authentication system with Micro SD.